Rotary motion characterization of tubular single excitation switched reluctance actuator - Yusri, Izzati (2017)
Precision motion system has been widely used in many applications either in industries as a pick and place robotic and semiconductor manufacturing processes or for small machines such as micro-gripper. Conventionally, the tasks are carried out using precision actuator that associates with the suitable controller and sensors to drive these actuators. Recently, the electromagnetic actuator is widely implemented to operate in rotary motion which leads to this research, i.e. rotary motion characterization of Switched Reluctance (SR) actuator using tubular single-excitation. The SR actuator is well known to have a highly non-linear characteristic and it suffers from uncontrolled motion’s behaviour. The main concern when achieving high precision motion is to suppress the non-linear characteristics of an actuator. Therefore, in this research, a SR actuator was design and evaluated in order to characterize the rotary motion characteristics. The research was divided into two main parts, i.e. (i) design of actuator through simulation work using Finite Element Method (FEM) analysis and (ii) actuator’s characterization through experimental works. In the design phase, four (4) parameters were optimized i.e.: (i) number of winding turns, N; (ii) stator-to-rotor poles ratio, S:R; (iii) air gap thickness, g and; (iv) stator-to-rotor arc angle, βs/βr. The optimization was conducted via simulation work through FEM analysis and the results were evaluated in terms of generated torque, flux density and saturation level. The SR actuator prototype was fabricated accordance to the optimized design with the actuator’s outer diameter 60mm and length 36mm, respectively. In this research, only Phase A was excited and called as the tubular single-excitation. This method is useful to obtain the motion characterization of SR actuator. The characterization of the SR actuator was carried out through open-loop experimental works. From the analysis, the rotor initial position at 0° was selected as the best initial position due to its highest generated torque. Based on the rotor initial positions at 0°, the linearizer unit was design namely RF0, where the function of the linearizer unit is to suppress the non-linear characteristics of the SR actuator. In addition, in order to improve the motion characteristics, the effects of three (3) signal waveforms were evaluated; i.e.: (i) step input; (ii) sine waveform and; (iii) pulse input signal. It was concluded that the pulse input signal, with 20Hz and 1:4 duty ratio was the suitable signal, which it was able to improve the SR actuator motion characteristics.